The Challenge of Terminographic Gaps in Translation: a Text-Based Approach Put to Practice - Mehrpooya, Abbas; Moinzadeh, Ahmad; Dabaghi, Azizollah (Research in Language, 2018)
The issue of terminographic gaps in specialized discourses has always concerned the researchers and readers alike. However, due to the interlingual nature of such a technical issue, the need for interdisciplinary collaboration between translation and terminography seems to be in prospect. For such a reciprocation scheme to come into practical effect, the present study has aimed to conduct a translational-terminographic concerto by putting a specialized English text to the test of Persian translation. This has been done to answer the question if a translator is required to provide for any terminological gap once all attempts at finding the corresponding terminological items have failed. In this pursuit, certain workable criteria for terminographic proposition via translation have been discussed. As such, the practical phase of this study concerns itself with addressing the issue of Persian terminological gaps in a language-related metadiscoursal field and consequently detecting the problem zones of non-equivalence in a specialised text carefully selected for translation. Ultimately, a list of Persian terminological items constructed on the basis of the proposed translational-cum-terminographical scheme is compiled to address the identified terminological gaps in the target metadiscourse under study.